Hubungan Pola Asuh Santri Dengan Adab Murid terhadap Guru di Pondok Pesantren Al Falak Pagentongan Bogor - Fani Fadilah; Fahmi Irfani; Nirwan Syafrin (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2022)
Adab (ethic/morality) of student toward his teacher is very important so that the knowledge obtained is a blessing and useful. But this blessing and benefit will not be immediately felt. Usually those blessing and benefits will only be realized in the future the knowledge gained being implemented in life. The adab of students bears a direct impact upon the teachers such that it can give a good motivation to the teacher: the teacher will feel good for us, be sincere, and pray good for us. The purpose of this study is to know the relationship between pattern of parenting the students with their ethic or morality towards their teachers in Pondok Pesantren Al Falak. This research is quantitative in nature. The study finds that the pattern of parenting in Pondok Pesantren Al Falak Pagentongan Bogor is inclined more towards authoritarian. This is evident from the number of respondents' answers which opt